Mental Health of Mothers with Stunted Children: Early Detection and Psychosocial Support - Ishmah Qonitatul Jannah; Sri Wahyuni; Jumaini Jumaini (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
Stunting is a chronic nutritional problem in children that has long-term effects on physical and mental growth. In addition, this condition also affects the mental health of mothers as primary caregivers. This study aims to describe the mental health conditions of mothers who have stunted children. The research design used is quantitative descriptive with a cross-sectional approach. The research sample consisted of 72 mothers selected using stratified sampling techniques, with inclusion criteria of mothers who had stunted children, were able to read and write, and lived with their children. The exclusion criteria were mothers who had been treated for mental disorders or were undergoing mental health treatment and mothers who were unwilling to be respondents. The instrument used was the SRQ-20 questionnaire developed by the WHO in 1994. Data analysis was performed univariately using frequency distribution and percentages. The results showed that the majority of mothers were aged 20–35 years (80.6%), had a high school education (69.4%), were housewives (77.8%), and had a family income below 3.5 million per month (76.4%). A total of 43 mothers (59.7%) did not experience mental health problems, while 29 mothers (40.3%) experienced mental health problems. The most common symptoms were fatigue (56.9%), difficulty sleeping (50%), and headaches (43.1%).